REVITALISASI KELEMBAGAAN KAMPUNG ADAT TENGAH KECAMATAN MEMPURA KABUPATEN SIAK - Mukhtar "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to examine the institutional revitalization of Indigenous Village Central District of Mempura Siak, where the revitalization program excludes Siak District Regulation No. 2 of 2015 Concerning Determination of Indigenous Village in Siak. Institutional revitalization of Indigenous Village Central is a form of empowerment customary law, which is expected to raise awareness about the rights and the existence of the community and the increased capacity so that customary law community is able to achieve access to the resources that exist, whether economic, social, political and cultural, as well as participating in all phases of the development process. In analyzing and explaining the results of this study, the authors used a qualitative research and analysis in this study used qualitative data analysis. The data discussed in this research is the answer from the results of interviews conducted with informants who have been determined by the authors, consisted of BPMPD Siak, Member of Parliament Siak who handle parts Institutional Indigenous Village, the Head of the Government Law Siak, LAMR Kabupaten Siak, Head Mempura, LAM District of Mempura, Penghulu Adat Kampung Tengah, Bapekam, clerk, Indigenous Stakeholder and public figures related. Results of research on Institutional revitalization of Indigenous Village Central District of Mempura Siak showed that: 1. Indigenous Village Central deserved to be Indigenous Village because it meets the criteria of Indigenous Village; 2. The community responded positively to the revitalization of Central Institutional Indigenous Village; 3. The process of revitalization of Indigenous Village Central Institutional concretely unmet due to the lack decree governing the technical implementation of the village of Indigenous and Indigenous Village code has not been issued by the Ministry of the Interior; 4. inhibiting factor in the revitalization process Institutional Indigenous Village Central District of Mempura Siak is still a lack of regulatory systems governing the Village People, people's participation and allocation of funds. Keywords: Revitalization, Institutional, Indigenous Village